2012
DOI: 10.1073/pnas.1120705109
|View full text |Cite
|
Sign up to set email alerts
|

Similarities of artificial photosystems by ruthenium oxo complexes and native water splitting systems

Abstract: The nature of chemical bonds of ruthenium(Ru)-quinine(Q) complexes, mononuclear ½RuðtrpyÞð3,5-t-Bu 2 QÞðOH 2 Þ ðClO 4 Þ 2 (trpy ¼ 2,2 0 : 6 0 ,2 0 0 -terpyridine, 3,5-di-tert-butyl-1,2-benzoquinone) (1), and binuclear ½Ru 2 ðbtpyanÞð3,6-di-Bu 2 QÞ 2 ðOH 2 Þ 2þ ðbtpyan ¼ 1,8-bisð2,2 0 : 6 0 ,2 0 0 -terpyrid-4 0 -ylÞanthracene, 3,6-t-Bu 2 Q ¼ 3,6-di-tertbutyl-1,2-benzoquinone) (2), has been investigated by broken-symmetry (BS) hybrid density functional (DFT) methods. BS DFT computations for the Ru complexes have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 46 publications
3
25
0
1
Order By: Relevance
“…Unlike other Ru‐based molecular catalysts, the Tanaka catalyst 6 , which is a non‐innocent quinone complex, maintains its Ru II centers during the redox process at the quinone and water units in achieving formation of oxyl radicals at a relatively low potential (0.4 V vs. Ag/AgCl). Theoretical and experimental results revealed that the removal of four protons from two molecules of water bound to ruthenium centers affords the corresponding two oxyl radicals and semiquinones via intramolecular charge transfer (Scheme ), and the subsequent four‐electron oxidation and the spin inversion achieved the O−O bond formation via intramolecular radical coupling of two oxyl species …”
Section: Catalytic Water Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other Ru‐based molecular catalysts, the Tanaka catalyst 6 , which is a non‐innocent quinone complex, maintains its Ru II centers during the redox process at the quinone and water units in achieving formation of oxyl radicals at a relatively low potential (0.4 V vs. Ag/AgCl). Theoretical and experimental results revealed that the removal of four protons from two molecules of water bound to ruthenium centers affords the corresponding two oxyl radicals and semiquinones via intramolecular charge transfer (Scheme ), and the subsequent four‐electron oxidation and the spin inversion achieved the O−O bond formation via intramolecular radical coupling of two oxyl species …”
Section: Catalytic Water Oxidationmentioning
confidence: 99%
“…molecular charge transfer (Scheme 4), and the subsequent four-electron oxidation and the spin inversiona chieved the OÀ Ob ond formationv ia intramolecular radicalc oupling of two oxyl species. [55][56][57] Thus, the quinone ligand functions as an efficient redox mediator in the oxidation of water by delocalizing electrons over the complex scaffold,a nd the radical coupling facilitates the formationo fabridged superoxide. One problem with that is that the replacement of the bridging peroxideb yw ater molecules is difficult within the rigid scaffold.…”
Section: Electrocatalytic Water Oxidationmentioning
confidence: 99%
“…Moreover, in breast cancer the presence of short telomeres coincides with a sudden rise in genomic instability at the transition from ductal hyperplasia to carcinoma in situ and before the activation of telomerase (Chin et al, 2004). This, together with the recent PCR-based detection of telomere fusions in early breast cancer, provides strong evidence for the occurrence of telomere crisis during breast cancer development (Tanaka et al, 2012). In addition, syndromes associated with telomere replication defects, such as dyskeratosis congenita and Werner syndrome, are characterized by short telomeres, genomic instability, and an elevated incidence of spontaneous cancer (Armanios and Blackburn, 2012).…”
Section: Understanding the Consequences Of Telomere Deprotectionmentioning
confidence: 82%
“…Wiei nA bbildung 2c dargestellt, folgt der Mechanismus der Wasseroxidation im PSII anerkanntermaßen einem S-Zyklus-Modell, an dem fünf Oxidationszustände beteiligt sind, die mit S 0 -S 4 bezeichnet werden (Kok-Zyklus). [72][73][74] [79][80][81][82][83][84][85][86][87][88] Iridium (Ir), [89][90][91][92][93][94] Mangan (Mn), [95,96] Molybdän( Mo), [97] Eisen (Fe), [98,99] Cobalt (Co), [100][101][102] Nickel (Ni) [103,104] und Kupfer (Cu). [105] Die Entwicklung von homogenen WOCw urde in vielen ausgezeichneten Übersichten bereits detailliert diskutiert.…”
Section: Wasseroxidationsmechanismenunclassified